First case of Wohlfahrtiimonas chitiniclastica isolation from a patient with a foot ulcer infection in Belgium. Issue 3 (4th May 2023) - De Smet, Delphine; Goegebuer, Truus; Ho, Erwin; Vandenbroucke, Michel; Lemmens, Ann
ABSTRACT: We present the first documented isolation of Wohlfahrtiimonas chitiniclastica from a patient in Belgium. The isolate was identified as W. chitiniclastica using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) and 16S rRNA gene sequencing. Our methodology corresponds with the previous conclusions on the superior performance of MALDI-TOF MS for bacterial identification. The patient was treated with amoxicillin/clavulanate and was discharged home after wound management. Although the clinical relevance of the isolate in our case is inconclusive, the pathogenicity of such isolate has been described and therefore must be considered as a potential pathogen in chronic and ulcerating wound cultures.